HUBUNGAN INDEKS MASSA TUBUH DENGAN Q ANGLE PADA SISWA SMA - Inggar Wati (2022)
Background: The additional load on the skeletal system in obese people results in changes in body mechanics that unfavorably affect joint function. Knee is part of the lower extremity that ensures stability of the body and receives high load pressure from body mass. Due to abnormal posture, it will dysfunction the lower extremity for everyday activity. Objective: To determine the relationship between Body Mass Index and Q angle in high school students. Methods: This research is a quantitative study which was compiled using an analytical observational research design with a cross sectional approach. With a total sample of 34 SMA Putra Bangsa students. Measurements of height and weight were carried out to determine the BMI value. Q-angle measurements were performed using a standard goniometer on both legs of the subject. Results: The data obtained from the Spearman test of BMI p-value with a right q-angle of 0.073 and a p-value of BMI with a left q-angle of 0.194 (p>0.05). It shows that there is no relationship between BMI and q-angle in high school students. Conclusion: Low q-angle scores are more common in male students and high q-angle scores are more commonly found in female students. The results of the hypothesis testing conducted in this study, body mass index did not have a correlation with the q-angle in high school students.